Caribou Conservation: Restoring Trees on Seismic Lines in Alberta, Canada - Angelo T. Filicetti; Michael Cody; Scott E. Nielsen (Forests, 2019)
Seismic lines are narrow linear (~3–8 m wide) forest clearings that are used for petroleum exploration in Alberta’s boreal forest. Many seismic lines have experienced poor tree regeneration since initial disturbance, with most failures occurring in treed peatlands that are used by the threatened woodland caribou (Rangifer tarandus caribou). Extensive networks of seismic lines, which often reach densities of 40 km/km2, are thought to have contributed to declines in caribou. The reforestation of seismic lines is therefore a focus of conservation. Methods to reforest seismic lines are expensive (averaging $12,500 per km) with uncertainty of which seismic lines need which treatments, if any, resulting in inefficiencies in restoration actions. Here, we monitored the effectiveness of treatments on seismic lines as compared to untreated seismic lines and adjacent undisturbed reference stands for treed peatlands in northeast Alberta, Canada. Mechanical site preparation (mounding and ripping) increased tree density when compared to untreated lines, despite averaging 3.8-years since treatment (vs. 22 years since disturbance for untreated). Specifically, treated lines had, on average, 12,290 regenerating tree stems/ha, which is 1.6-times more than untreated lines (7680 stems/ha) and 1.5-times more than the adjacent undisturbed forest (8240 stems/ha). Using only mechanical site preparation, treated seismic lines consistently have more regenerating trees across all four ecosites, although the higher amounts of stems that were observed on treated poor fens are not significant when compared to untreated or adjacent undisturbed reference stands.